44 Parents' and clinicians' reconceptualisation of the future for children with high-risk brain tumours as revealed in consultations and home visits. (15th December 2021) - Beecham, Emma; Langner, Richard; Hargrave, Darren; Bluebond-Langner, Myra
Abstract : Background: Throughout the illness trajectory parents and clinicians face a number of decisions that impact the child's future. The future parents once envisaged is threatened. Parents reconceptualise that future in response. Aims: To explore: 1) how the future is conceptualised during conversations between clinicians and parents; 2) how parents' and clinicians' concept of the future changes over the course of the illness trajectory. Methods: 20-month ethnographic study of 19 families including observation and audio-recording of 244 interactions among children with high-risk brain tumours, parents and clinicians. We present results from an interactionist analysis of 48 verbatim transcripts (42 consultations; 6 home visits) where the child's future was discussed. Results: Parents and clinicians began to reconceptualise their views of the child's future at the time of diagnosis and continued to do so throughout the illness. Children's views remained relatively stable from diagnosis and hence are not included here. Before recurrence of disease, clinicians focused on the close horizon, on getting on with treatment whilst helping families to reconceptualise and manage expectations on the distant horizon. After progression, positions reversed. Parents' vision of their child's future shortened. They focused on pursuing further treatment. Clinicians, however, emphasised the impact treatment would have on the child's future as the child's condition deteriorated and cure was not possible. At the end of life, parents and clinicians focused increasingly on the present and making use of time left. Conclusion: Parents' and clinicians' conceptualisation of the child's future varied over time, aligning only at end of life. In the interest of optimising communication, clinicians need to maintain awareness of changing views around the child's future. A shared perspective aids in shared decision making and best management of symptoms and well-being throughout the child's life.